The Challenges of E-Learning for Higher Education Lecturers and Learners - Marsevani, Maya (Journal of Education Technology, 2022)
The use of E-Learning in the English language learning process is very useful for stakeholders, especially lecturers and learners. But in reality, lecturers and learners often experience difficulties in using it both from a technical and non-technical perspective. This study aims to investigate the challenges faced by EFL lecturers and learners and how they face them. To overcome this problem, this research employed a case study. This study involved 244 learners and 12 lecturers to fill out a questionnaire and five of them were interviewed. To collect questionnaire data, this research used a google form, meanwhile, the researcher carried it out online using the zoom application for interviewing respondents. After collecting the data, the results of the questionnaire were processed using IBM SPSS software and the interview results were described qualitatively. The results showed that lecturer constraints include lack of time to develop E-Learning content, inability to optimally utilize E-Learning features, problems in lecturer-learner interaction, poor internet connection, and lack of learner motivation. Meanwhile, the challenges of learners include the lack of tools to access E-Learning, lack of motivation, technical problems, and barriers to E-Learning features. It can be concluded that lecturers and learners face challenges both technically and non-technically in using E-Learning. The implication of this research is that despite all the challenges faced, lecturers and learners are required to be able to adapt to E-Learning environment in order to facilitate the online learning process.